Ballooning and Bursting of Barrels and Pipes: A Rare Case of Suspected Vascular Ehlers–Danlos Disease - Ogechi Agogbuo; Sri Harsha Kanuri; Luis Salinas; Mohamed Goweba; Khashayar Vahdat; Oscar Chastian; Larry Frase (Cardiogenetics)
Vascular Ehler–Danlos disease (vEDS), a rare subtype of a rare disease, is a life-threatening disease, with an increased risk for spontaneous vascular or visceral rupture. These patients have fatal complications ranging from vascular aneurysms, dissection, and rupture of systemic vessels to frequent thromboembolic events, the common causes of death in these individuals with a shortened life span. In the present case, a 28-year-old male with history of shoulder dislocations and spontaneous colon perforation presented to the primary care clinic with right lower extremity swelling and pain. His history includes presentation to the emergency department with left lower leg swelling with compartment syndrome one year prior. A CT angiogram of lower extremities and abdomen revealed acute arterial extravasation of the left posterior tibial artery, indicating a ruptured aneurysm along with aneurysms of the splenic artery and left common iliac artery. He was treated with a saphenous vein graft, but was associated with post-operative complications that necessitated below-knee amputation. CT angiogram of his right leg revealed occlusion of the anterior tibial and peroneal arteries with aneurysms, and, ultimately, he was referred to a tertiary care center for aneurysm embolization. This case report emphasizes the frequent vascular complications encountered in vascular EDS patients, and thus advocates for close and regular monitoring for early referral and surgical management of their vascular anomalies. Finally, genetic counseling and screening of asymptomatic family members should be routinely implemented in these patients.